Is Coefficient of Variation a Realistic Index for Characterizing Mixing Efficiency in Ozone Applications?. (3rd March 2020) - Pathapati, Srikanth. S.; Smith, Daniel W.; Bennett, Justin P.; Mazzei, Angelo L.
ABSTRACT: The coefficient of variation (COV) of ozone residual is often used to compare the mixing performance of different ozone contacting systems. Multiphase mass transfer CFD modeling is performed and compared with experimental data to investigate the correlation between mass transfer efficiency, a corresponding full cross-sectional spatial COV, a corresponding "grab sample" temporal COV, and a comprehensive uniformity index for mixing for varying sidestream ozone doses. Typical sampling methodology for ozone residual is reviewed and general guidelines for better representative sampling are suggested.